Influência da sazonalidade sobre as águas estuarinas dos furos da ilha de Colares (baía do Marajó) - GUIMARÃES, Robledo Hideki Ebata (Universidade Federal do Pará, 2015)
The characterization of surface and interstitial waters in estuaries is critical to unravel the environmental conditions, environmental quality and seasonal changes, which may occur in smaller space such as the hole in the island of Colares. This work aims to show the influence of seasonality in estuarine waters in the north and south of the mouth of the hole island of Colares and the contribution of pore waters to surface waters. The physical and chemical parameters and nutrients are included: rainfall (IP), temperature, salinity, pH, electrical conductivity, total dissolved solids, suspended particulate matter, dissolved oxygen, Secchi depth, nitrate, nitrite, N-ammonia, phosphate, silicate and sulfate. The determination of these parameters occurred simultaneously in each mouth of the hole necklaces over a tidal cycle (13 hours) in rainy (04/10/2013) and drier (10/05/2013) periods. The results show that seasonality affects abiotic conditions of estuarine waters bore the island of Colares and deduces that P1 is the most important factor to effect the changes of physical and chemical parameters, and especially the higher charge mobility, availability and distribution of dissolved nutrients, which were found in higher concentrations in the rainy season. Although the nutrients nitrate and N-ammonia were considered very high at the mouth North, possibly related to the influence of anthropogenic activities. However were considered within the limits established by CONAMA Resolution 357/05. Mouth occurred in South pH levels outside the standard stipulated by Resolution CONAMA, but the phenomenon was considered natural since in this specific is distant from anthropogenic activities. In less rainy period the N-ammonia was found to be absent in mouth North and South. The mangrove was considered as a source of salinity, silicate and sulfate to surface waters.